HUBUNGAN ANTARA PEMAHAMAN GAMBAR KERJA DAN HASIL BELAJAR TEORI TEKNIK PEMESINAN BUBUT DENGAN HASIL BELAJAR PRAKTIK TEKNIK PEMESINAN BUBUT SISWA KELAS XI SMK MUHAMMADIYAH PRAMBANAN TAHUN AJARAN 2015/2016 - Dwi Widi Astowo; Setuju Setuju (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this study was to determine: (1) the relationship of understanding of working drawings to learning outcomes practices lathe machining techniques; (2) the relationship of learning outcomes lathe machining engineering theory with practice learning outcomes lathe machining techniques; and (3) the relationship of understanding of working drawings and learning outcomes lathe machining engineering theory with practice learning outcomes lathe machining technique class XI student of SMK Muhammadiyah Prambanan Academic Year 2015/2016. This research is a correlation study. Members of the study population consisted of 149 students. Samples were taken based on the formula slovin is 110 students. Sampling was conducted using Proportional Random Sampling technique. In this research, there are two independent variables that relationship understanding of working drawings and learning outcomes theory lathe machining techniques, as well as the dependent variable is the result of learning practices lathe machining techniques. Methods of data collection using tests and documentation.Data were analyzed using partial correlation formula and double correlation. The results of this study indicate that: (1) there is a positive and significant relationship between the understanding of working drawings to learning outcomes practices lathe machining techniques. Evidenced by the price of r count larger than r 0.285 0.186 table. It shows that the higher a person's understanding of working drawings, the higher the learning outcomes the lathe practice machining techniques; (2) There is a positive and significant relationship between learning outcomes lathe machining engineering theory with practice learning outcomes lathe machining techniques. Evidenced by the price of r count larger than r 0.250 0.186 table. It shows that the higher the yield learning theory lathe machining techniques a person, the higher the learning outcomes the lathe practice machining techniques; and (3) There is a positive and significant relationship between the understanding of working drawings and learning outcomes theory lathe machining techniques together with the learning outcomes the lathe practice machining techniques. Evidenced by the price of R = 0.372 and p = 0.000 smaller than 0.05. It shows that thehigher a person'sunderstanding of working drawings and learning outcomes theory lathe machining techniques a person, the higher the learning outcomes the lathe practice machining techniques.